2016
DOI: 10.1103/physrevb.93.014434
|View full text |Cite
|
Sign up to set email alerts
|

Ba2YIrO6: A cubic double perovskite material withIr5+ions

Abstract: Materials with a 5d 4 electronic configuration are generally considered to have a nonmagnetic ground state (J = 0). Interestingly, Sr2YIrO6 (Ir 5+ having 5d 4 electronic configuration) was recently reported to exhibit long-range magnetic order at low temperature and the distorted IrO6 octahedra were discussed to cause the magnetism in this material. Hence, a comparison of structurally distorted Sr2YIrO6 with cubic Ba2YIrO6 may shed light on the source of magnetism in such Ir 5+ materials with 5d 4 configuratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
129
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(164 citation statements)
references
References 31 publications
20
129
2
Order By: Relevance
“…This is in line with the observation by Dey et al The amount of Y 2 O 3 increases to 6% in BYIO-4d-Q and 11% in BYIO-16d. Dey et al 9 proposed that the observed Y 2 O 3 exists as inclusions in crystals. While this is quite likely, we occasionally observe under optical microscope isolated Y 2 O 3 in BYIO-16d.…”
Section: A X-ray Powder Diffraction and Thermopowermentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with the observation by Dey et al The amount of Y 2 O 3 increases to 6% in BYIO-4d-Q and 11% in BYIO-16d. Dey et al 9 proposed that the observed Y 2 O 3 exists as inclusions in crystals. While this is quite likely, we occasionally observe under optical microscope isolated Y 2 O 3 in BYIO-16d.…”
Section: A X-ray Powder Diffraction and Thermopowermentioning
confidence: 99%
“…al. 9 suggested the magnetism in Ba 2 YIrO 6 was due to paramagnetic impurities. In a later study 11 , they identified a Schottky anomaly in the specific heat of Sr 2 YIrO 6 pointing to the conclusion that paramagnetic impurities are responsible for the observed Curie susceptibilities without the onset of long range magnetic order.…”
Section: 10mentioning
confidence: 99%
“…Several experimental realizations of excitonic magnetism have already been discussed in the literature. [19][20][21][22][23] Model. We use the dynamical mean-field theory (DMFT) to study the minimal model of an excitonic magnet -the two-orbital Hubbard Hamiltonian at half- filling…”
mentioning
confidence: 99%
“…In tetravalent (Ir 4+ ) 5d 5 iridates, such as Sr 2 IrO 4 [8][9][10], a complex spin-orbit entangled J eff = 1/2 state is realized, with a reduced bandwidth due to the splitting from the J eff = 3/2 states, which leads to the localization of electrons even by a relatively small on-site Coulomb interaction compared to their 3d counterparts. Additional effects of SOC include XY anisotropy [11,12], locking of the magnetic moment to the correlated rotation of oxygen octahedra in Sr 2 IrO 4 [13], anisotropic dimer excitations in Sr 3 Ir 2 O 7 [14], and Kitaev-type magnetic interactions in Na 2 IrO 3 [15].…”
mentioning
confidence: 99%
“…Recent focus has been on new iridate compounds where experimental discoveries have strongly challenged theoretical predictions. For example, in pentavalent (Ir 5+ ) 5d 4 iridates a strong SOC is predicted to realize a nonmagnetic J = 0 state [4], but substantial magnetic moments have been found in Ba 2 YIrO 6 [5] and especially in Sr 2 YIrO 6 [6], where structural distortion of the octahedral environment leads to 0.91 μ B /Ir. Furthermore, a possible realization of a spinorbital liquid with Ir 5+ has been discussed for 6H hexagonal Ba 3 ZnIr 2 O 9 powder [7].…”
mentioning
confidence: 99%